Keberhasilan Pemberian Asi Eksklusif Pada Primigravida - Julung Susanto; hamdayani hamdayani; Sainah Sainah (Patria Artha Journal of Nursing Science, 2024)
Primigravida mothers are pregnant women for the first time. The lack of understanding of primigravida mothers about exclusive breastfeeding can cause problems in exclusive breastfeeding after the mother gives birth to a baby, this can occur due to lack of knowledge. Knowledge can be associated with one's education. The purpose of this study was to determine the relationship between primigravida education level and the success of exclusive breastfeeding. This research method uses correlational descriptive with a cross sectional approach. The sample size is 48 primigravida mothers at Bhayangkara TK Hospital. III Balikpapan, East Kalimantan. The results showed that most of the respondents with higher education were successful in providing exclusive breastfeeding (88.2%), respondents with secondary education were not successful in exclusive breastfeeding (72.2%) and respondents with primary education were unsuccessful in providing exclusive breastfeeding (92, 3%). The results of the Spearman Rho test obtained a p value of 0.000 < (Î± = 0.05) with a correlation level of 0.661 which indicates Ha is accepted so that it is concluded that there is a strong relationship between the level of primigravida education and the success of exclusive breastfeeding, where the higher the level of education, the higher the level of The success of exclusive breastfeeding. It is hoped that primigravida mothers can seek information related to exclusive breastfeeding regarding the benefits and advantages for mothers and babies so that they can provide exclusive breastfeeding correctly